PENGARUH MEDIA PEMBELAJARAN BERBASIS VIDEO TERHADAP MINAT BELAJAR DAN HASIL BELAJAR SISWA KELAS VIII SMPK SANTO YUSUP MOJOKERTO - Simbolon, Widi Herianto; Permana, Natalis Sukma (CREDENDUM: Jurnal Pendidikan Agama, 2021)
This study aims to determine the effect of video on students' interests and learning outcomes. Video media learning is one of the learning media that is currently very widely used by teachers in learning because video media is a simple and interesting learning media because it can display media in a various ways such as combining image and sound media. The main problem in this study is the lack of use of learning media by teachers during process so the effect is that students tend to feel bored and less focused when the teacher explains learning material, especially on the material for the sacrament of baptism. This can be seen from the increased interest and student learning outcomes when learning to use video media. The research method used in this study was an experiment (pre-experimental design) in the form of one group pretest-post-test. Methods of data analysis using SPSS 16 for windows software. The results showed that video had a positive effect with an R-value of 0.474 on students' interest and learning outcomes at SMPK Santo Yusup Mojokerto.